STRONG GROUND-MOTION PREDICTION FROM STOCHASTIC-DYNAMIC SOURCE MODELS - Guatteri M.; Mai P.M.; Beroza G.C.; Boatwright J. (My University, 2003)
In the absence of sufficient data in the very near source, predictions of the intensity and variability of ground motions from future large earthquakes depend strongly on our ability to develop realistic models of the earthquake source. In this article we simulate near-fault strong ground motion using dynamic source models. We use a boundary integral method to simulate dynamic rupture of earthquakes by specifying dynamic source parameters (fracture energy and stress drop) as spatial random fields. We choose these quantities such that they are consistent with the statistical properties of slip heterogeneity found in finite-source models of past earth- quakes. From these rupture models we compute theoretical strong-motion seismo- grams up to a frequency of 2 Hz for several realizations of a scenario strike-slip Mw 7.0 earthquake and compare empirical response spectra, spectra obtained from our dynamic models, and spectra determined from corresponding kinematic simulations. We find that spatial and temporal variations in slip, slip rise time, and rupture prop- agation consistent with dynamic rupture models exert a strong influence on near- source ground motion. Our results lead to a feasible approach to specify the vari- ability in the rupture time distribution in kinematic models through a generalization of Andrews' (1976) result relating rupture speed to apparent fracture energy, stress drop, and crack length to 3D dynamic models. This suggests that a simplified rep- resentation of dynamic rupture may be obtained to approximate the effects of dy- namic rupture without having to do full dynamic simulations.